ALTERNATIF PENJUALAN AGUNAN EMAS UNTUK MENAIKKAN HARGA DALAM RISIKO GAGAL BAYAR DI PEGADAIAN SYARIAH ATMO, PALEMBANG - Herlina, Herlina; Siska, Emi Yulia; Janati, Nurlaili (Komunitas Manajemen Kompetitif, 2025)
Customers often experience the risk of default in a financing due to weakened financial conditions. The purpose of the research is to select sales that maintain the value of the collateral so that it is not valued lower than the market price. This research uses a qualitative approach with a comparative level of explanation and is field research. The type and strategy of research findings are case studies. The place of research was at Atmo Sharia Pawnshop Palembang and several gold shops in the Megahria area of Palembang. The process of taking, collecting, and analyzing data is carried out simultaneously by conducting observations, interviews, and field tests on several relevant and accurate cases. The results showed that with the risk of default experienced by customers, the collateral must be sold to cover the outstanding. Customers who face this condition usually automatically sell the collateral to the financial institution that finances it, in this case Pegadaian Syariah. The fact that occurs in the field is that there is a price difference between the selling value in the market (gold shop) and the estimated value in the pawnshop. The customer should first conduct a survey of the fair market value of the collateral and determine the alternative of selling the collateral in the right place, namely the gold shop. The method used by the customer is to deal with the pawnshop staff in the form of a proposal to sell the collateral on the market. With the approval of the pawnshop, then bargain with the gold shop to see the condition of the collateral in the pawnshop and immediately make a transaction. This step is a safe and appropriate way for all three parties, namely the pawnshop, the customer, and the gold shop. From the discussion, it can be concluded that customers must be observant in updating the price or market value of the collateral and be able to determine alternative places to sell collateral properly and accurately. Keywords: Pawnshop, Syariah, Collateral, Gold, Sales.